Social Marketing for Health Equity: Promoting Preventive Health Behavior Among Women in Rural Communities - Mouloudj, Kamel; Alameri, Sarah Ali Saeed; Evans, Marian A.; Almado, Alaa Abdulkareem Ghaleb; Mahmoud, Basheer Ismail; Asanza, Dachel Martínez (International Journal of Environmental Research and Public Health, 2026)
Preventive health behaviors play a critical role in reducing disease risks and improving public health outcomes, particularly among vulnerable populations such as women in rural communities. However, limited research has explored the determinants of intentions to adopt preventive health behaviors in developing contexts among women in rural communities. This study applies and extends the Theory of Planned Behavior (TPB) to examine these determinants in Algeria. A cross-sectional study was conducted using convenience sampling among 205 women in rural communities aged 20–60 years across five Algerian cities. Data were collected through a self-administered questionnaire and analyzed using hierarchical multiple regression. The results indicate that attitude, subjective norms, and perceived behavioral control have significant positive effects on behavioral intention. The inclusion of health literacy significantly enhances the model’s explanatory power, with higher literacy associated with stronger intentions. In contrast, perceived healthcare discrimination does not have a statistically significant effect. The extended model explains 57.5% of the variance in behavioral intention. These findings underscore the importance of psychosocial and informational factors in shaping preventive health intentions and support the extension of TPB in this context. They also provide practical implications for policymakers and healthcare practitioners to design targeted social marketing interventions aimed at improving preventive health behaviors and reducing health disparities among women in rural communities. © 2026 by the authors.
Keywords: Behavior change; Health belief model; Health care; Health literacy; Health promotion; Psychological intervention; Psychosocial; Public health; Social marketing; Theory of planned behavior; dept.pch; health equity; health literacy; health policy; perceived healthcare discrimination; preventive health behaviors; women in rural communities